1989
DOI: 10.1677/joe.0.1220005
|View full text |Cite
|
Sign up to set email alerts
|

The role of hypothalamic vasoactive intestinal polypeptide in the maintenance of prolactin secretion in incubating bantam hens: observations using passive immunization, radioimmunoassay and immunohistochemistry

Abstract: The role of chicken vasoactive intestinal polypeptide (cVIP) as a prolactin-releasing factor was investigated in incubating bantam hens. Specific antibodies were raised against cVIP (anti-cVIP) for passive immunization studies, to develop a radioimmunoassay and to localize VIP neurones immunohistochemically in the hypothalamus. The concentration of plasma prolactin decreased after i.v. injection of anti-cVIP: this low concentration being maintained by daily injection of anti-cVIP. Incubating hens injected dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(85 citation statements)
references
References 30 publications
6
77
1
1
Order By: Relevance
“…VIP-immunoreactive cells have been localized within the mediobasal hypothalamus and external median eminence in several avian species (Yamada & Mikami 1982, Macnamee et al 1986, Peczely & Kiss 1988, Mauro et al 1989. Changes in the number and size of VIP immunoreactive cells have been demonstrated to parallel plasma concentrations of PRL in chickens (Sharp et al 1989), turkeys (Mauro et al 1989) and doves (Cloues et al 1990). Hypothalamic VIP content, VIP mRNA abundance and the affinity of anterior pituitary VIP-binding sites have been shown to be positively correlated with the concentration of plasma PRL in turkeys (Mauro et al 1992, Rozenboim & El Halawani 1993, You et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…VIP-immunoreactive cells have been localized within the mediobasal hypothalamus and external median eminence in several avian species (Yamada & Mikami 1982, Macnamee et al 1986, Peczely & Kiss 1988, Mauro et al 1989. Changes in the number and size of VIP immunoreactive cells have been demonstrated to parallel plasma concentrations of PRL in chickens (Sharp et al 1989), turkeys (Mauro et al 1989) and doves (Cloues et al 1990). Hypothalamic VIP content, VIP mRNA abundance and the affinity of anterior pituitary VIP-binding sites have been shown to be positively correlated with the concentration of plasma PRL in turkeys (Mauro et al 1992, Rozenboim & El Halawani 1993, You et al 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Cessation of egg laying is associated with increased concentrations of plasma prolactin (Etches, Garbutt, and Middleton, 1979;Burke and Dennison, 1980;Lea et al, 1981;Bluhm, Phillips, and Burke, 1983;Hall and Goldsmith, 1983;Silverin and Goldsmith, 1983), and in turkeys and domestic fowl (Sharp, Macnamee, Sterling, Lea, and Pedersen, 1988), administration of exogenous prolactin suppresses plasma gonadotropins necessary for egg production. However, there is additional evidence that the suppression of gonadotropin secretion in incubating birds also involves a mechanism independent of increased prolactin secretion (Sharp et al, 1988;Lea and Sharp, 1989;Sharp, Sterling, Talbot, and Huskisson, 1989;Lea, Richard-Yris, and Sharp, 1996).…”
mentioning
confidence: 99%
“…Much earlier studies also reported that higher prolactin concentrations were present in the pituitary gland at this specific physiological stage (Riddle et al, 1935;Saeki and Tanabe, 1955 El Halawani et al, 1980;Proudman and Opel, 1981;Zadworny et al, 1985) whereas its disruption using pharmacological treatments (El Halawani et at, 1983;Gu6men6 and Etches, 1989) Sharp, 1996) were effective in preventing or delaying its occurrence. It has also been shown, both in mammals (Neri et al, 1964;Ferin et at, 1968;Goldman et at, 1972) and birds (Lea et al, 1981;Sharp et al, 1989;Lea et at, 1991) …”
mentioning
confidence: 88%
“…(Sharp et al, 1989). Likewise, intracranial perfusion of prolactin had no effect upon LH levels (Youngren et al, 1991 (Lea et al, 1981).…”
Section: Radioimmunoassaymentioning
confidence: 99%